The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1101/2022.08.22.504793
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chromosome 9p21.3 Coordinates Cell Intrinsic and Extrinsic Tumor Suppression

Abstract: SUMMARYSomatic chromosomal deletions are prevalent in cancer, yet their functional contributions remain ill-defined. Among the most prominent of these events are deletions of chromosome 9p21.3, which disable a cell intrinsic barrier to tumorigenesis by eliminating the CDKN2A/B tumor suppressor genes. However, half of 9p21.3 deletions encompass a cluster of 16 type I interferons (IFNs) whose co-deletions have not been functionally characterized. To dissect how 9p21.3 and other genomic deletions impact cancer, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 83 publications
1
1
0
Order By: Relevance
“…This highlights the importance of determining mechanisms of 9p band somatic alteration–related immune modulation in different tumor types, especially if these genomic features are to be used as biomarker tests to guide precision ICT. In PAAD, for example, we found that 9p21.3 loss was the prominent driver of low immune score/CD8 T cells, in accordance with recent evidence in pancreatic cancer mouse models ( 43 ).…”
Section: Discussionsupporting
confidence: 90%
“…This highlights the importance of determining mechanisms of 9p band somatic alteration–related immune modulation in different tumor types, especially if these genomic features are to be used as biomarker tests to guide precision ICT. In PAAD, for example, we found that 9p21.3 loss was the prominent driver of low immune score/CD8 T cells, in accordance with recent evidence in pancreatic cancer mouse models ( 43 ).…”
Section: Discussionsupporting
confidence: 90%
“…Loss of chromosome arm 9p or parts thereof has been proposed to be used as an alternative to TMB or PD-L1 staining for ICB efficacy predictions [31,32]. This is likely due to deletions encompassing the Interferon gene cluster, which are often found to be co-deleting the tumour suppressor locus CDKN2A, rendering cells less immunocompetent and more proliferative [33].…”
Section: The Immune System and Cancer-specific Immune Evasion Mechanismsmentioning
confidence: 99%